Taqālīd “Ḥarb” Topat: Ramz al-‘Alāqah al-Silmīyah bayn al-Jamā‘āt al-Mukhtalifah ‘Ariqīyā wa-Dīnīyā fī Jazīrat Lombok - Suprapto Suprapto (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2011)
This article discusses about perang topat tradition in West Lombok, West Nusa Tenggara. Perang topat is one of the annual ceremonies attended by thousands of people of the two different ethnic and religious communities: the Hindu Balinese and the Muslim Sasak. The location of performing this tradition is concentrated in a sanctum (Hindus called it Pura Lingsar and Muslim named it Taman Lingsar) which is located near to Selaparang airport, Mataram. Pura Lingsar is built by the King Anak Agung Gede Ngurah of Karang Asem, Bali. Pura Lingsar is a Hindus' house of worship which, aside from a place of worship, it also has a building named kemalik that is considered as a sacred place by Sasak people.DOI: 10.15408/sdi.v18i3.428